Asuhan Kebidanan Paripurna Pada Ibu Hamil Risiko Tinggi dengan Anemia - Bherta Yuceline H.S; Estin Gita Maringga; Nunik Ike Yunia Sari (PT FORMOSA CENDEKIA GLOBAL, 2022)
The condition of high-risk pregnant women is a condition that really needs monitoring. The purpose of this case study is to minimize the incidence of complications in Ny.